The ghettos of Pan-Africanism - Araoye, Lasisi Ademola (Austin. Texas Ibadan Pan-African University press, 2021)
"The Ghettos of Pan-Africanism excavates the tortuous trajectory of the struggle for totalistic emancipation of black humanity and affirms the undiminished integrity of the axioms encapsulated in Pan-Africanism as a philosophy of radical action for that elusive emancipation. The Ghettos is against the background of strenuous attempts at counterfeited deflections of the original ideas of Pan-Africanism through politically driven contentious reinterpretations of the philosophy on the home continent and increasing ethnicization of black humanity in the Diaspora through direct and nuanced repudiation of the essences of the black self. These deflections of the philosophy and physical defections from the race are often for narrow and convenient ends. The Ghettos of Pan-Africanism revalidates the original understandings of Pan-Africanism as a race-based radicalized voice articulating the centrality of the unity of black people in pursuit of the common destiny of that one race. Pan-Africanism was never based on the aggregation of states burnishing mere fictive sovereignties in their odious reinforced silos of massive human misery. African states are highlighted as sore fixations in aborted transition validated by the anti-people political entrepreneurs (poliprenuers) who double as proxies of the inimical external order and their human agency in the inimical external Other. The Ghettos illustrates the consequences of this in the pervasive malignancy of African statehood that is understood as an accursed impediment to the fulfillment of the emancipation thrust of black struggle. In practical terms, the rejection of Pan Africanism as the fundamental underpinning of political evolution by Africa's wounding fathers in Addis Ababa in 1963 is adduced as the source of the consolidation of Africa and black humanity along the tangents of relevance in the affairs of humanity"--
Inlcude Index
Keywords: Pan-Africanism.